Molecular insights into enriched environments and behavioral improvements in autism: a systematic review and meta-analysis - Li, Yutong; Lu, Jing; Zhang, Jing; Gui, Wenxin; Xie, Weijie (Frontiers in Psychiatry, 2024)
Aims Autism is a multifaceted developmental disorder of the nervous system, that necessitates novel therapeutic approaches beyond traditional medications and psychosomatic therapy, such as appropriate sensory integration training. This systematic mapping review aims to synthesize existing knowledge on enriching environmental interventions as an alternative avenue for improving autism, guiding future research and practice. Method A comprehensive search using the terms ASD and Enriched Environment was conducted across PubMed, EMBASE, ISI, Cochrane, and OVID databases. Most of the literature included in this review was derived from animal model experiments, with a particular focus on assessing the effect of EE on autism-like behavior, along with related pathways and molecular mechanisms. Following extensive group discussion and screening, a total of 19 studies were included for analysis. Results Enriched environmental interventions exhibited the potential to induce both behavioral and biochemical changes, ameliorating autism-like behaviors in animal models. These improvements were attributed to the targeting of BDNF-related pathways, enhanced neurogenesis, and the regulation of glial inflammation. Conclusion This paper underscores the positive impact of enriched environmental interventions on autism through a review of existing literature. The findings contribute to a deeper understanding of the underlying brain mechanisms associated with this intervention.